The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2000
DOI: 10.1088/0031-9155/45/12/301
|View full text |Cite
|
Sign up to set email alerts
|

Objective comparison of image quality and dose between conventional and synchrotron radiation mammography

Abstract: The shape of the energy spectrum produced by an x-ray tube has a great importance in mammography. Many anode-filtration combinations have been proposed to obtain the most effective spectrum shape for the image quality-dose relationship. On the other hand, third generation synchrotrons such as the European Synchrotron Radiation Facility in Grenoble are able to produce a high flux of monoenergetic radiation. It is thus a powerful tool to study the effect of beam energy on image quality and dose in mammography. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…The following images from the ROI of the MAMMAX breast phantom were experimentally obtained: (a) a single (14,16,18,20,22,24,26, and 27 keV) used to synthesize polychromatic images that correspond to an incident x-ray spectrum with W target.…”
Section: Iib Acquisition Scenariosmentioning
confidence: 99%
“…The following images from the ROI of the MAMMAX breast phantom were experimentally obtained: (a) a single (14,16,18,20,22,24,26, and 27 keV) used to synthesize polychromatic images that correspond to an incident x-ray spectrum with W target.…”
Section: Iib Acquisition Scenariosmentioning
confidence: 99%
“…Taking these theoretical advantages into consideration, many research groups have worked on applying and evaluating SR for breast imaging. [10][11][12][13][14][15] Burattini et al 10,11 performed SR mammograms on both phantoms and breast specimens that had also been irradiated with conventional mammographic units, concluding that SR results improved image quality for energies of 17 and 18 keV, while keeping the dose at the same level. Johnston et al 12 noticed an increased image contrast in images taken with a monoenergetic beam compared to conventional mammographic spectra, especially in the case of energies above 18 keV.…”
Section: Introductionmentioning
confidence: 99%
“…Johnston et al 12 noticed an increased image contrast in images taken with a monoenergetic beam compared to conventional mammographic spectra, especially in the case of energies above 18 keV. Moeckli et al 13 also worked on comparing SR to conventional mammography in terms of image quality and dose using test objects. The group of the Elettra Synchrotron Radiation Facility in Trieste has been dealing with SR mammography for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and experimental studies have demonstrated the existence of an optimum energy range both for diagnostic radiology [28][29][30] and mammography examinations. [19][20][21][31][32][33] For example, improvement in image contrast and reduction of patient dose in mammography can be achieved using narrow energy-band x-ray beams in the range of 17-24 keV. Increasingly higher energies become more and more detrimental to the intrinsic image contrast, because of the vanishingly small difference between attenuation coefficients of lesions and normal tissues.…”
Section: Introductionmentioning
confidence: 99%